PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI BADAN LAYANAN UMUM DAERAH (BLUD) RUMAH SAKIT MAYJEN HM. RYACUDU LAMPUNG UTARA - Junaedi, Ahmad (Universitas Sang Bumi Ruwa Jurai, 2017)
Problems in this research are: (1) Does the work motivation affect the performance of employees of the Regional Public Service Institution of HM. Ryacudu Hospital North Lampung (2) Does the work discipline affect the performance of employees of the Regional Public Service Institution of HM. Ryacudu Hospital North Lampung (3) Does the motivation of work and work discipline affect the performance of employees of the Regional Public Service Institution of HM. Ryacudu Hospital North Lampung. The purpose of research to analyze and know: (1) The influence of work motivation on the performance of employees of the Regional Public Service Institution of HM. Ryacudu Hospital North Lampung. (2) The influence of work discipline on the performance of employees of the Regional Public Service Institution of HM. Ryacudu Hospital North Lampung. (3) The influence of work motivation and work discipline on the performance of employees of the Regional Public Service Institution of HM. Ryacudu Hospital North Lampung. This research uses explanatory survey method by analyzing the effect of work motivation and work discipline as independent variable and performance of employee Regional Public Service Institution of HM. Ryacudu Hospital North Lampung as the dependent variables. The research population is 575 employees, while the sample is 10% that is 58 people. Data collection techniques used, questionnaires, interviews, observation and documentation. The analytical technique used to analyze data is the statistic formula of Multiple Linear Regression. The results showed that: (1) Work motivation positively and significantly affect the performance of employees of the Regional Public Service Institution of HM. Ryacudu Hospital North Lampung. (2) Work discipline has a positive and significant influence on the performance of employees of the Regional Public Service Institution of HM. Ryacudu Hospital North Lampung. (3) Simultaneously work motivation and work discipline have an effect on positively and significantly to employee performance of Regional Public Service Institution of HM. Ryacudu Hospital North Lampung.